Effects of individual characteristics and seasonality and their interaction on ectoparasite load of Daurian ground squirrels in Inner Mongolia, China - Xiaoxu Wang; Meng Shang; Zihao Wang; Haoqiang Ji; Zhenxu Wang; Guangju Mo; Qiyong Liu (International Journal for Parasitology: Parasites and Wildlife)
Understanding the drivers of parasite distribution is vital for ecosystem health, disease management, and vector monitoring. While studies note the impact of host sex, size, behavior, and season on parasite load, concurrent assessments of these factors and their interactions are limited. During the spring, summer and autumn seasons from 2021 to 2023, we trapped Daurian ground squirrel (Spermophilus dauricus), a small rodent species that inhabits eastern Asian grasslands in Inner Mongolia and collected their ectoparasites. Using machine learning Lasso regression, we pinpointed factors affecting tick and flea abundance on S. dauricus. We then analyzed these factors and their seasonal interactions with a mixed negative binomial generalized linear model. Our study revealed significant but inconsistent seasonal effects on the load of ectoparasites. The tick load was significantly higher in spring and summer compared to autumn, while the flea load was higher in summer and autumn but lacked statistical significance. Furthermore, individual factors that influence the flea and tick load were moderated by seasonal effects, with a male bias in flea parasitism observed in spring. Significant interactions were also found among seasonality, sex, and body weight. The load of male squirrel fleas was positively correlated with body weight, with the highest increase observed in spring. On the contrary, the flea load of female squirrels showed a negative correlation with body weight, significantly decreasing in the autumn with increasing weight. Significant interactions were observed between season and survival status, with hosts exhibiting higher tick load during autumn survival. Our findings underscore the importance of considering seasonal variation in parasitism and the interactions between seasonal dynamics and host biological traits in shaping parasite distributions.